A SIGNIFICANCE OF ETHICS AND DEONTOLOGY IN THE PROFESSIONAL RESPONSIBILITIES OF THEOLOGIANS (Web of Teachers: Inderscience Research, 2025)
This paper explores the significance of ethics and deontology in the professional activities of theologians. It examines how moral principles and professional codes guide their interpretation of religious texts, interactions with communities, and involvement in interfaith dialogue. The study employs a qualitative methodology to analyze both classical and contemporary sources. The findings highlight the indispensable role of ethical responsibility and deontological frameworks in preserving the credibility and moral authority of theologians.